Latent responsive sentences in modern English - Суима, Ирина Павловна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article deals with the research of latent responsive sentences on the basis of the modern English language. Special attention is given to the semantic, structural and functional peculiarities of the syntactic units under research. The main types of the latent responsive sentences are described. Definitions for the terms “responsive sentence” and “responsive” are suggested. The linguistic and extralinguistic factors influencing latent responsive sentences in the dialogic speech are considered. Special attention is paid to the sphere of functioning of the given syntactic units.